2003
DOI: 10.1096/fj.02-0830fje
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin‐1 mediates platelet adhesion at high shear via glycoprotein Ib (GPIb): an alternative/backup mechanism to von Willebrand factor

Abstract: Acute thrombotic arterial occlusion is the leading cause of morbidity and mortality in the Western world. Von Willebrand factor is thought to be the only indispensable adhesive substrate to promote thrombus formation in high shear environments. We found that thrombospondin-1, a glycoprotein enriched in arteriosclerotic plaques, might function as an alternative substrate for thrombus formation. Platelets adhered to thrombospondin-1 in a shear dependent manner with an optimum shear as found in stenosed arteries.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
96
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(102 citation statements)
references
References 46 publications
2
96
0
3
Order By: Relevance
“…Our study showed the critical role for the platelet GPIb␣, because the replacement of its extracellular domain resulted in abnormal angiogenesis. Beside VWF and P-selectin, GPIb has other ligands such as the leukocyte integrin Mac-1 (54) and thrombospondin I (55). In addition, GPIb is a thrombin receptor and binds other coagulation factors (56).…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed the critical role for the platelet GPIb␣, because the replacement of its extracellular domain resulted in abnormal angiogenesis. Beside VWF and P-selectin, GPIb has other ligands such as the leukocyte integrin Mac-1 (54) and thrombospondin I (55). In addition, GPIb is a thrombin receptor and binds other coagulation factors (56).…”
Section: Discussionmentioning
confidence: 99%
“…First discovered in platelets as a thrombin-sensitive protein (1), THBS1 was later shown to be a major component of platelet ␣-granules, comprising some 25% of the total protein (2). Once released, THBS1 exerts various functions on the vascular system under physiological and pathophysiological conditions causing platelet activation (3,4) and adhesion (5) in addition to endothelial cell adhesion (6), promotion of angiogenesis (7), and inhibition of angiogenesis (8), wound healing (9) as well as pathological states such as tumor progression and metastasis (10,11). THBS1 is important not only in cancer progression but also in inflammatory autoimmune diseases such as rheumatoid arthritis (12).…”
mentioning
confidence: 99%
“…cruzi must navigate the ECM in order to infect mammalian cells. Amongst the glycoproteins of the ECM, thrombospondins constitute a set of unique multidomain proteins that are synthesized, secreted and incorporated into the ECM by many cell types (115)(116). Thrombospondins are unique members of the ECM in that they have been described as 'matricellular' proteins because they modulate cell function but they do not play a direct role in the structure of the ECM.…”
Section: Thrombospondin-1mentioning
confidence: 99%